Information technology. Spyware. - Bergren MD (Journal of School Nursing, 2004)
School nurses access an enormous amount of information through the Internet. Although most avid computer users are savvy to the threat of viruses to the integrity of data, many who surf the Web do not know that their data and the functioning of their computer is at risk to another hidden threat--spyware. This article will describe spyware, why it is a problem, how it is transmitted to a personal or business computer, how to prevent spyware infestation, and how to delete it.